2012
DOI: 10.7314/apjcp.2012.13.9.4567
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Importance of Women with Squamous Cell Carcinoma Cytology on Siriraj Liquid-Based Cervical Cytology

Abstract: Objectives: The purposes of this study were to determine the prevalence and predictive value to detect significant neoplasia and invasive lesions, and to evaluate the correlation between clinical and histopathology of women with squamous cell carcinoma (SCCA) on Siriraj liquid-based cervical cytology (Siriraj-LBC). Methods: The computerized database of women who underwent Siriraj-LBC at Siriraj Hospital, Mahidol University from January 2007 to December 2010 were retrieved. The hospital records of women with SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(19 reference statements)
2
1
0
Order By: Relevance
“…The PPV for CIN2+ increased with types of abnormal cytology, from 13.69% to 93.82%, in ASCUS, LSIL, ASC-H, abnormal glandular cytology, HSIL, and SCC, respectively. These results were comparable with the results in the first year of Siriraj-LBC and in other studies (Dupree et al, 1998;Papillo et al, 1998;Diaz-Rosario and Kabawat, 1999;Fremont-Smith et al, 2004;Ruengkhachorn et al, 2012). Our 4-year data strongly indicated that Siriraj-LBC, a low cost LBC technology, was qualified for cervical cancer screening.…”
Section: Discussionsupporting
confidence: 92%
“…The PPV for CIN2+ increased with types of abnormal cytology, from 13.69% to 93.82%, in ASCUS, LSIL, ASC-H, abnormal glandular cytology, HSIL, and SCC, respectively. These results were comparable with the results in the first year of Siriraj-LBC and in other studies (Dupree et al, 1998;Papillo et al, 1998;Diaz-Rosario and Kabawat, 1999;Fremont-Smith et al, 2004;Ruengkhachorn et al, 2012). Our 4-year data strongly indicated that Siriraj-LBC, a low cost LBC technology, was qualified for cervical cancer screening.…”
Section: Discussionsupporting
confidence: 92%
“…Another study by Aue-aungkul et al (2011), in evaluating the clinical feasibility of the see and treat approach in managing Thai women with abnormal cervical cytology, from the same hospital reported that approximately 55.6% of women with SCCA cytology had invasive cervical lesions. An extraordinarily high incidence of underlying invasive lesion in women with SCCA cytology was concordantly found in recent reports from the other areas of Thailand by Ruengkhachorn et al (2012) and Kingnate et al (2014): 82.5% and 77.4% respectively. Thus, a high likelihood of harboring invasive disease in Thai women with SCCA smears should be kept in mind while taking care of women with SCCA cytology.…”
Section: Squamous Cell Carcinoma Cytologysupporting
confidence: 86%
“…A number of non-FDA-approved methods have been developed for use outside of the USA. These include LiquiPrep [4], Turbitec [5], PapSpin [6], TACAS [7,8], Siriraj-LBC [9], DNA-Citoliq (Digene) [10], GluCyte [11], and some other devices [12,13]. Specimen materials collected in the preservation medium are routinely used for cell blocks, which can provide additional diagnostic information, including architectural pattern, immunocytochemistry (ICC) and special stains.…”
Section: Introductionmentioning
confidence: 99%